Serum resistin levels in benign prostate hyperplasia and non-metastatic prostate cancer: possible role in cancer progression - Housa, Daniel; Vernerová, Zdenka; Heráček, Jiří; Čechák, Petr; Rosová, Blanka; Kuncová, Jitka; Haluzík, Martin (Neoplasma, 2008)
Resistin is a member of adipokine family involved in the regulation of inflammatory reactions and insulin sensitivity. In presented study its possible role in the development of benign prostate hyperplasia and prostate cancer was evaluated. Blood samples and prostate specimens were collected from 26 patients with benign prostate hyperplasia (BPH) and from 42 patients with prostate cancer (PCa) stage pT2 (n=18) and pT3 (n=24). Selected metabolic and biochemical parameters and serum resistin levels were measured and anthropometric measurements were performed as well as tissue immunohistochemistry for resistin. Serum resistin levels did not differ significantly between benign hyperplasia and prostate cancer but in cancer patients there was a trend towards decrease with higher cancer stage. Moreover, serum resistin levels were significantly lower in patients with seminal vesicle invasion in comparison to those without invasion. While in BPH serum resistin levels correlated with insulin resistance, inflammatory status and cortisol, in PCa positive correlation with F/T PSA ratio and cortisol was observed. Tissue immunohistochemistry did not show any differences in staining pattern between benign and neoplastic prostate tissue. We conclude that serum resistin levels do not significantly differ between patients with benign prostate hyperplasia and prostate cancer, but there is a trend towards decrease in resistin serum levels in advanced cancer cases.
Keywords: nádory prostaty; Neoplasm Staging; lidé; Disease Progression; alopecie; Alopecia; Prostatic Hyperplasia; Financing, Organized; financování organizované; Aged; Humans; staging nádorů; senioři; progrese nemoci; hyperplazie prostaty; resistin; Prostatic Neoplasms; Resistin